Gun Violence Exposure and Posttraumatic Symptoms Among Children and Youth. Issue 6 (12th December 2019) - Turner, Heather A.; Mitchell, Kimberly J.; Jones, Lisa M.; Hamby, Sherry; Wade, Roy; Beseler, Cheryl L.
Abstract: Although statistics on youth homicide and injury from gun violence are available, little research has focused on how gun violence overlaps with other victimizations or on the psychological impact of gun violence on children. Pilot survey data were collected on the experiences of 630 U.S. children (age range: 2–17 years) from Boston, Philadelphia, and rural areas of eastern Tennessee. Youth aged 10–17 years completed a self‐report survey on a wide range of gun violence exposures, and parents of younger children (aged 2–9 years) completed the survey as a proxy for that child. Direct gun violence exposure, witnessing gun violence, and hearing gunshots were all significantly associated with other forms of victimization, r s = .10–.38, p < .001. The findings suggest that youth who experience direct gun violence are often exposed to multiple violent contexts. For older youth (ages 10–17 years) polyvictimization was most strongly associated with posttraumatic symptoms, β = .35, p < .001, although witnessing gun violence still uniquely predicted a higher level of symptoms, β = .18, p < .01. For younger children (ages 2–9 years), hearing and witnessing gun violence were both related to posttraumatic symptoms, β = .15, p < .01 for both, even after controlling for polyvictimization. Mental health professionals and trauma‐informed services should be mindful that the traumatic impact of gun violence for children may not necessarily be attached to direct victimization experiences but may also result from simply seeing or hearing it in their neighborhoods. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Exposición a la violencia con armas de fuego y síntomas de trauma en niños y jóvenes VIOLENCIA CON ARMAS DE FUEGO Y SÍNTOMAS POSTRAUMÁTICOS EN JOVENES Aunque existen estadísticas sobre homicidios y lesiones por violencia con arnas de fuego en jóvenes, poca investigación se ha enfocado en cómo la violencia con armas de fuego se superpone con otras victimizaciones o en el impacto psicológico de la violencia con armas de fuego en niños. Se recopilaron datos de encuestas piloto sobre las experiencias de 630 niños estadounidenses (rango de edad: 2–17 años) de Boston, Filadelfia y áreas rurales del este Tennesse. Jóvenes de 10 a 17 años completaron una encuesta de autoinforme sobre una amplia gama de exposición a violencia con armas de fuego, y los padres de niños más pequeños (de 2 a 9 años) completaron la encuesta como representantes de esos niños. Exposición directa a la violencia con armas de fuego, presenciar violencia con armas de fuego y escuchar los disparos se asociaron significativamente con otras formas de victimización, rs = .10 – .38, p < .001. Los resultados sugieren que los jóvenes que sufren violencia directa con armas de fuego a menudo están expuestos a múltiples contextos violentos. Para los jóvenes mayores (de 10 a 17 años), la poli‐victimización fue más fuertemente asociada con síntomas postraumáticos, β = .35, p <.001, aunque el ser testigo de violencia con arma de fuego predijo únicamente un nivel de síntomas más altos, β = .18, p <.01. Para los niños más pequeños, escuchar y presenciar la violencia con armas de fuego se relacionaron ambos con síntomas postraumáticos, β = .15, p s <.01, incluso después de controlar por la poli‐victimización. Los profesionales de salud mental y los servicios informados de trauma deben tener en cuenta que el impacto traumático de la violencia por armas de fuego en los niños no necesariamente está asociado a las experiencias de victimización directa, sino que también pueden simplemente ser el resultado de verlo o escucharlo en sus vecindarios. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Gun Violence Exposure and Trauma Symptoms among Children and Youth Traditional Chinese 標題: 兒童和青少年的槍擊案經歷與創傷症狀 撮要: 雖然坊間已有青少年因槍擊案而喪生或受傷的統計數字, 但少有研究針對槍擊案如何跟其他受害事件同時影響著受害人, 或槍擊案對兒童造成的心理影響。我們透過630名於美國波士頓、費城、田納西州東部郊區的兒童 (年齡值域:2–17 歲) 的經驗, 取得先導的問卷數據。10–17歲的青少年完成了一個有關廣泛的槍擊案經歷的自評問卷, 而年齡較小的兒童 (2–9 歲) 則由家長代為完成問卷。直接的槍擊案經歷、目擊槍擊案、聽到槍聲都顯著地跟其他類型的受害經歷有關 (rs = .10–.38, p < .001) 。結果反映, 曾直接經歷槍擊案的青少年常處於有多種暴力的環境。在年齡較大的青少年 (10–17歲) 中, 多創傷多數跟創傷後症狀有最強的關連 (β = .35, p < .001), 即使目擊槍擊案仍然獨特地預測到較高水平的症狀 (β = .18, p < .01) 。在年齡較小的兒童中, 即使對多創傷作對照後, 聽到和目擊槍擊案都跟創傷後症狀有關 (β = .15, ps < .01) 。心理治療專業人士和創傷治療服務提供者都應留意, 槍擊案對兒童帶來的創傷影響並不一定由直接的受害經歷所致, 亦有可能單單因目擊或聽到附近的槍擊案引致。 Simplified Chinese 标题: 儿童和青少年的枪击案经历与创伤症状 撮要: 虽然坊间已有青少年因枪击案而丧生或受伤的统计数字, 但少有研究针对枪击案如何跟其他受害事件同时影响着受害人, 或枪击案对儿童造成的心理影响。我们透过630名于美国波士顿、费城、田纳西州东部郊区的儿童 (年龄值域:2–17 岁) 的经验, 取得先导的问卷数据。10–17岁的青少年完成了一个有关广泛的枪击案经历的自评问卷, 而年龄较小的儿童 (2–9 岁) 则由家长代为完成问卷。直接的枪击案经历、目击枪击案、听到枪声都显著地跟其他类型的受害经历有关 (rs = .10–.38, p < .001) 。结果反映, 曾直接经历枪击案的青少年常处于有多种暴力的环境。在年龄较大的青少年 (10–17岁) 中, 多创伤多数跟创伤后症状有最强的关连 (β = .35, p < .001), 即使目击枪击案仍然独特地预测到较高水平的症状 (β = .18, p < .01) 。在年龄较小的儿童中, 即使对多创伤作对照后, 听到和目击枪击案都跟创伤后症状有关 (β = .15, ps < .01) 。心理治疗专业人士和创伤治疗服务提供商都应留意, 枪击案对儿童带来的创伤影响并不一定由直接的受害经历所致, 亦有可能单单因目击或听到附近的枪击案引致。